2013
DOI: 10.1097/paf.0b013e31828879cd
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Limitations of Triphenyltetrazolium Chloride to Detect Acute Myocardial Infarction at Forensic Autopsy

Abstract: Triphenyltetrazolium chloride (TTC) is one of the most conventional stains to detect infarcted area of the heart in animal experiments. However, its availability and limitations have not been thoroughly discussed in the forensic field. Here, authors stained human hearts with TTC soon after the harvest. Photographs of the samples were analyzed using image analysis software, which evaluated the occupying ratio of the stained area on the surface of each slice. The results showed that the stainability of TTC decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…In fact, ischemic heart failure, the main cause of sudden cardiac death, scarcely displays any abnormal morphological changes 12 h after the initial acute myocardial infarction (AMI) [ 1 ]. Histological staining methods, such as triphenyltetrazolium chloride (TTC) staining, are often useful when visualizing the infarcted myocardial area during the sub-acute phase; however, these techniques are incapable of grossly detecting morphological changes in the early phase of AMI [ 2 ]. Therefore, it is essential to investigate novel biomarkers whose expression levels change rapidly during AMI.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, ischemic heart failure, the main cause of sudden cardiac death, scarcely displays any abnormal morphological changes 12 h after the initial acute myocardial infarction (AMI) [ 1 ]. Histological staining methods, such as triphenyltetrazolium chloride (TTC) staining, are often useful when visualizing the infarcted myocardial area during the sub-acute phase; however, these techniques are incapable of grossly detecting morphological changes in the early phase of AMI [ 2 ]. Therefore, it is essential to investigate novel biomarkers whose expression levels change rapidly during AMI.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,5-Triphenyltetrazolium chloride (TTC) is a redox indicator that produces water insoluble red formazan crystals when reduced [ 4 ]. It has been used extensively for several decades as an indicator of tissue ischaemia [ 5 , 6 ], and more recently to detect the presence of live micro-organisms based on metabolic activity of intracellular enzymes [ 4 ]. Accumulation of TTC within live bacteria provides high contrast between bacterial colonies and several solid agar media.…”
Section: Resultsmentioning
confidence: 99%
“…In an article concerning the effectiveness of triphenyltetrazolium chloride to detect acute myocardial infarction, the authors state that "it is not realistic to apply methods confirmed in animals" [68]. Stokes et al observed contrasting dynamics of mammalian analogues in experimental taphonomy, and state that "the results of this study showed many differences between porcine, bovine, and ovine SMTs (skeletal muscular tissues) when considering them as analogues for human SMT2 in decomposition soil studies" [69].…”
Section: Discussionmentioning
confidence: 96%
“…From this point of view, the history of forensic sciences has provided us with much evidence of the inapplicability of data obtained from studies performed on animal models, including the Daubert sentence [66] and several recent studies have again stressed the limits of this approach in different fields of forensic sciences, from the estimation of post mortem interval to genetics [67][68][69][70][71][72][73][74][75]. In an article concerning the effectiveness of triphenyltetrazolium chloride to detect acute myocardial infarction, the authors state that "it is not realistic to apply methods confirmed in animals" [68].…”
Section: Discussionmentioning
confidence: 99%